PERAN AGAMA DALAM PROSES REKRUTMEN TENAGA PENDIDIK DI PENDIDIKAN ISLAM - Tulili, Ammalia; Jamilus, Jamilus (Faculty of Teacher Training and Education, 2025)
Education is the foundation of national development. Through education, individuals can develop their potential, understand social values, and contribute to the progress of society. Quality education emphasizes not only academic aspects but also the formation of character and individual morality. In this regard, Islamic education plays a very important role because it integrates values with general knowledge. Islamic education focuses not only on the transfer of knowledge but also on the development of solid character. In the Quran, Allah SWT says,